Consecutive negative findings on colonoscopy during surveillance predict a low risk of advanced neoplasia in patients with inflammatory bowel disease with long-standing colitis: results of a 15-year multicentre, multinational cohort study. Issue 4 (2nd May 2018) - ten Hove, Joren R; Shah, Shailja C; Shaffer, Seth R; Bernstein, Charles N; Castaneda, Daniel; Palmela, Carolina; Mooiweer, Erik; Elman, Jordan; Kumar, Akash; Glass, Jason; Axelrad, Jordan; Ullman, Thomas A; et al.
Abstract : Objectives: Surveillance colonoscopy is thought to prevent colorectal cancer (CRC) in patients with long-standing colonic IBD, but data regarding the frequency of surveillance and the findings thereof are lacking. Our aim was to determine whether consecutive negative surveillance colonoscopies adequately predict low neoplastic risk. Design: A multicentre, multinational database of patients with long-standing IBD colitis without high-risk features and undergoing regular CRC surveillance was constructed. A 'negative' surveillance colonoscopy was predefined as a technically adequate procedure having no postinflammatory polyps, no strictures, no endoscopic disease activity and no evidence of neoplasia; a 'positive' colonoscopy was a technically adequate procedure that included at least one of these criteria. The primary endpoint was advanced colorectal neoplasia (aCRN), defined as high-grade dysplasia or CRC. Results: Of 775 patients with long-standing IBD colitis, 44% (n=340) had > 1 negative colonoscopy. Patients with consecutive negative surveillance colonoscopies were compared with those who had at least one positive colonoscopy. Both groups had similar demographics, disease-related characteristics, number of surveillance colonoscopies and time intervals between colonoscopies. No aCRN occurred in those with consecutive negative surveillance, compared with an incidence rate of 0.29 to 0.76/100 patient-years (P=0.02) in those having > 1 positive colonoscopy on follow-up of 6.1 (P25–P75: 4.6–8.2) years after the index procedure. Conclusion: Within this large surveillance cohort of patients with colonic IBD and no additional high-risk features, having two consecutive negative colonoscopies predicted a very low risk of aCRN occurrence on follow-up. Our findings suggest that longer surveillance intervals in this selected population may be safe.